2020
DOI: 10.5039/agraria.v15i4a8572
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal variation of wood quality in the five forest species from Caatinga

Abstract: The present study aimed to evaluate the dendrometric and chemical characteristics and variation of basic density and moisture content (green) of the wood of five Caatinga forest species along the commercial longitudinal direction (base-top) of logs. The studied species were pau-branco (Auxemma oncocalyx (Fr. All.) Taub.), jurema preta (Mimosa tenuiflora (Willd.) Poir.), jurema-de-embira (Mimosa ophthalmocentra Mart. ex Benth.), pereiro (Aspidosperma pyrifolium Mart.) and sabiá (Mimosa caesalpiniifolia Benth.).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The samples initial mass (air dried) was recorded. Physical and chemical analyses of these samples were performed in a previous study of our group (Batista et al 2020a), and the results are shown in Figure 2a and Figure 2b. The CCA-C treated Eucalypts wood (Eucalyptus sp.)…”
Section: Species Location and Wood Samplesmentioning
confidence: 99%
“…The samples initial mass (air dried) was recorded. Physical and chemical analyses of these samples were performed in a previous study of our group (Batista et al 2020a), and the results are shown in Figure 2a and Figure 2b. The CCA-C treated Eucalypts wood (Eucalyptus sp.)…”
Section: Species Location and Wood Samplesmentioning
confidence: 99%
“…Experiments were undertaken from January to March 2019 at the forest nursery at Universidade Federal Rural do Semi-árido, in Mossoró, Rio Grande do Norte state. According to Kö ppen's classifi cation, the climate of the municipality is classifi ed as BSh, that is, dry semiarid climate, the average temperature of the region is 27.4 °C, with average relative humidity of 68.9%, very irregular annual rainfall, with an average of 673.9 mm and a drought period of 6 to 8 months (Melo et al, 2020).…”
Section: Implantation and Management Of The Clonal Minigardenmentioning
confidence: 99%
“…Among native caatinga species, Sabiá (Mimosa caesalpiniifolia Benth. ), stands out for its rustic and fast-growing nature, being recommended for shading, to act as living fence, forage, recovery of degraded areas, and source of wood for stakes, fencepost, fi rewood and charcoal (Balbinot et al, 2010;Araujo and Paes, 2018;Batista et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to Rebouças et al (2018), it is the most promising native species for reforestation in the region, mainly due to its fast growth, high biomass productivity, good drought resistance, and carbon fi xation ability. Other properties, such as high wood density, higher calorifi c value, and contents of volatile matter and ash, allow the species to be used for energy generation (Santos et al, 2013;Batista et al, 2020). Besides these features, M. caesalpiniifolia has a good capacity for regeneration after harvesting (Podadera et al, 2015), and its bark has a high content of condensed tannins (Marques et al, 2021).…”
Section: Introductionmentioning
confidence: 99%